Collaboration is a key skill : so why aren't we teaching it? - Mashek, Deb (MIT Sloan Management Review, 2022)
A survey of 1,100 full-time U.S. employees found that people spend an average of 3.2 hours per workday collaborating with others. But despite the importance of workplace collaboration, most organizations devote little time to educating their workers on how to build healthy and productive collaborative relationships. The author discusses the survey results’ implications and offers six suggestions for helping individuals, teams, and organizations develop their collaboration skills.